Evaluasi Pengembangan Kompetensi Preceptor Klinis Keperawatan Melalui Pelatihan Preceptorship Di RSUD Cibabat Cimahi - Yunita Fitri Rejeki; Annisa Nur Erawan (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
The aim of this research was evaluating the development of clinical preceptor competencies of RSUD Cibabat Cimahi through preceptorship training. The design of the research was quasi experimental. The results of the study revealed that the pre-test score of Component A 94,5% (17 respondents) was “moderate”, component B 55,5% (10 respondents) was “deficient”, component C 77,7% (14 respondents) was “deficient”, and component D 83,3% (15 respondents) was “moderate”. The posttest results revealed that component A, B, C, and D was 100% (18 respondents) were “fine”. Bivariate analysis deployed Wilcoxon Test, showed that the p value was 0,001 (< 0,05) then Ha is accepted. Conclusions of the study, there was positive differences between pre-test and posttest results after given preceptorship training to the clinical instructor. Suggestion, continuous preceptorship training program may be developed by RSUD Cibabat Cimahi which is dedicated to the clinical instructor. Moreover, the respondents of the research should be evaluated three months after the training.